Sport-related concussion disclosure in women's rugby—A social identity approach - Ryan, Lisa; Daly, Ed; Blackett, Alexander D. (Frontiers in Sports and Active Living, 2023)
Sport-related concussion (SRC) is a risk of collision sports such as women’s rugby. To support appropriate SRC diagnosis and management, an understanding of the factors that encourage SRC disclosure is necessary. To date, research has focused on ascertaining individual player knowledge and attitudes towards SRC disclosure. We chose to investigate the potential influence of group identification effects by examining the role of social identity on SRC disclosure in elite women’s rugby. Seventeen elite players from the UK and Ireland were interviewed and their transcripts thematically analysed. The data highlighted that the players shared a very strong social identity as women in rugby and were acutely aware that their experiences were different to their male counterparts. The shared social identity had both positive and negative implications for SRC disclosure. Mediators such as communication, trust in medical teams, perceived pressure, positive injury management experience and player role models were identified. This research could be utilised to inform sport psychology interventions to enhance SRC disclosure in elite women’s rugby.